Analisis Peran Konsultan Pajak Dalam Meningkatkan Kepatuhan Wajib Pajak Di KPP Pratama Jakarta Koja Tahun 2021 - Hesti Agustin; Bambang Irawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The role of the Tax Consultant is very influential for taxpayers who do not understand regarding tax regulations, based on the Regulation of the Minister of Finance of the Republic of Indonesia Number 111/PMK.03/2014 concerning Tax Consultant Number 1, the Tax Consultant is a person who provide tax consulting services to taxpayers to exercise their rights, and fulfill its tax obligations by laws and regulations. This study aims to analyze the Role of Tax Consultants in improving Taxpayer Compliance at the Jakarta Pratama Tax Service Office Koja, then what are the obstacles that hinder it taxes consultants in increasing taxpayer compliance as well as the efforts made in overcome these obstacles. This research was conducted using qualitative methods with this type of research descriptive, the data source consists of primary data which is interview and observation data and secondary data using tax reporting documents. The result of this study indicate that the role of the tax consultant has self-confidence (Role Conception), the taxpayer’s expectation of the consultant’s role, as well as the implementation of the role the tax consultant has been properly implemented as recorded or stated in the report tax, but there are still several things that must be improved implementing role.